Avaliação das ações de prevenção e vigilância à influenza aviária, desenvolvidas pelo Programa Nacional de Sanidade Avícola PNSA, no período de 2004 a 2007 - Marcelo de Andrade Mota (2012)
Brazil has established itself as world's largest exporter of chicken meat since 2000. To ensure health status and the maintenance of the international Brazilian poultry markets it was organized official AI surveillance strategies. Between 2004 and 2005, it monitored1,064 municipalities in commercial poultry production, located in 14 Brazilian states. It was collected 106,226 sera and 7,017 tracheal and cloacae swabs. GIS was used to visualize the distribution of serological results. One epidemiological cluster was identified, located in Rondônia State, obtained after interpolation of ELISA positive reactions resultsand the municipalities geographic position. The serological tests results were not sufficient to demonstrate absence of prior exposure of commercial poultry to AI viruses in 6 Brazilian states. There were no positive results for IA viral isolation in tested samples. For2006 and2007 period, The Brazilian Ministry of Agriculture, Livestock and Food Supply has developed three AI virus surveillance protocols 1) Commercial poultry broilers. The samples were obtained at commercial broilers operations that presented 10% cumulative mortality rate. 13,295 sera and 883 pools of tracheal and cloacae swabs were collected. 2)Breeding poultry flocks. 373 batches were tested at 20th week of age. It was collected 5,593 serum samples from birds with no AI clinical signs. 3) Wild migratory birds and back yard poultry. 363 migratory wild bids belonging to Anseriformes and Charadriiforme orders were caught in 20 different sites. It was investigated 118 municipalities, with properties ofbackyard poultry. It was collected 2,865swabs for AI virological research. No antibody response or AI virus isolation succeed in commercial broilers or breeding poultry samples. H2, H3 and H4 LPAI subtypes viruses were isolated in backyard poultry samples. H3 LPAI AI virus was isolated in samples from migratory birds.